8+11y-1=6y+79-3y

Simple and best practice solution for 8+11y-1=6y+79-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+11y-1=6y+79-3y equation:


Simplifying
8 + 11y + -1 = 6y + 79 + -3y

Reorder the terms:
8 + -1 + 11y = 6y + 79 + -3y

Combine like terms: 8 + -1 = 7
7 + 11y = 6y + 79 + -3y

Reorder the terms:
7 + 11y = 79 + 6y + -3y

Combine like terms: 6y + -3y = 3y
7 + 11y = 79 + 3y

Solving
7 + 11y = 79 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
7 + 11y + -3y = 79 + 3y + -3y

Combine like terms: 11y + -3y = 8y
7 + 8y = 79 + 3y + -3y

Combine like terms: 3y + -3y = 0
7 + 8y = 79 + 0
7 + 8y = 79

Add '-7' to each side of the equation.
7 + -7 + 8y = 79 + -7

Combine like terms: 7 + -7 = 0
0 + 8y = 79 + -7
8y = 79 + -7

Combine like terms: 79 + -7 = 72
8y = 72

Divide each side by '8'.
y = 9

Simplifying
y = 9

See similar equations:

| 6h-7=11 | | 4[x+4]+12=0 | | 8-3=3 | | -8x+4(2-3x)=36-6x | | 6+6/6*6+6=24 | | 6k-8=4k+5 | | 3/4x^2-2x+7 | | -2+n/2=0 | | x=92+20y | | 12.88t-103.04=5.52t-44.16 | | -18=18p-(33-2p) | | -11/-143 | | 10b+18=86+4 | | 11+4n=7-n | | 3x-28=3x-30 | | 3.50p(5.50+6.00)=51.00 | | -5+4*(-3)+2*9-(-6)= | | 8(n+6)=-36-4n | | c+9.09=-4.41 | | 40s+18t-5t+11a= | | 3+4x+2x^2-4x-x^2= | | 5(x+2)=x+6(x+3) | | 22+7v=4v+7(5v-6) | | 8+4m=gm-11 | | 2b/3+81=20 | | 3y+12=-48 | | r-7.2=4.56 | | 4+x=x+6 | | 8(x+5)=7(x+3) | | 17=3p+15+8 | | 8x-25=3d | | -3-(-9)+5-11= |

Equations solver categories